Trans-inactivation: Repression in a wrong place - Aleksei S. Shatskikh; Yuriy A. Abramov; Sergey A. Lavrov (Fly, 2017)
Trans-inactivation is the repression of genes on a normal chromosome under the influence of a rearranged homologous chromosome demonstrating the position effect variegation (PEV). This phenomenon was studied in detail on the example of brownDominant allele causing the repression of wild-type brown gene on the opposite chromosome. We have investigated another trans-inactivation-inducing chromosome rearrangement, In(2)A4 inversion. In both cases, brownDominant and In(2)A4, the repression seems to be the result of dragging of the euchromatic region of the normal chromosome into the heterochromatic environment. It was found that cis-inactivation (classical PEV) and trans-inactivation show different patterns of distribution along the chromosome and respond differently to PEV modifying genes. It appears that the causative mechanism of trans-inactivation is de novo heterochromatin assembly on euchromatic sequences dragged into the heterochromatic nuclear compartment. Trans-inactivation turns out to be the result of a combination of heterochromatin-induced position effect and the somatic interphase chromosome pairing that is widespread in Diptera.